Adaptation of a lime incorporation equipment for soils under no-tillage (Revista de Ciências Agroveterinárias, 2007)
No tillage (NT) is an excellent soil management system, whose advantages have been corroborated by its widespread use. However, two aspects of this system may restrict crop yield: soil compaction and the high concentration of nutrients on the soil surface and of toxic elements to root system development on the subsurface, due to the application of correctives and fertilizers exclusively on the topsoil. This study aimed to design an equipment capable of eliminating compaction and placing lime into NT soils. The equipment was designed to chisel plow the soil up to a depth of 25 cm, and to incorporate lime through a tube mounted on the rear edge of the chisel shank, using a mechanical metering system and a pneumatic injection/transportation system. Soybean was cropped using four no-till soil management systems and grain yield was assessed. The results of several mechanical assessments were positive, despite the fact that lime was concentrated in an area of approximately 20 cm in diameter around the shank. In the area that was chisel plowed and limed, grain yield was 818 kg ha-1 higher than in NT soils that were not chisel plowed and not limed. The results show that the proposed equipment is an alternative to mitigate physical and chemical constraints to root system development in the soil profile, increasing soybean grain yield.
Keywords: soil compaction; physical attributes; chemical attributes.